Shoaling Upward Cycles (Parasequences) and their Significance in the Black River -Trenton Carbonates (Ordovician) of Southern Ontario, Canada - Muftah El Gadi (AlQalam Journal of Medical and Applied Sciences, 2023)
The Black River and Trenton Groups form a thin (average 150 metres) transgressive systems tract of a Middle to Upper Ordovician carbonate depositional sequence. Within this tract, various upward shoaling cycles bounded by flooding surfaces (parasequences) can be used for local correlation. The Black River contains symmetrical and asymmetrical low energy ‘lagoonal’ - supratidal cycles within a generally deepening (backstepping) succession. Flooding surfaces are marked by various condensed ‘glauconitic’ horizons with a marine, though somewhat low-diversity, fauna. The facies can be directly compared with those of the modern Persian Gulf. The Black River- Trenton boundary is a major flooding surface separating a ‘lagoonal’-tidal flat succession (Black River) from an open marine succession (Trenton Group). This change is practically synchronous from Lake Simcoe to Kingston and marks either a relatively rapid and significant rise in relative sea-level, or an erosion surface caused by shelf reworking between depositional shoreline and deep shelf facies. Interpretations of this open shelf succession are difficult due to major biological changes since the Ordovician; though the ‘shaved shelf’ depositional model may be more appropriate than current conventional models. The Trenton Group also contains asymmetrical and symmetrical cycles (like the Jurassic Klupfel cycles of western Europe), whose resistant capping grainstones form persistent and mappable units over much of southern Ontario. Like Klupfel cycles, the Trenton cycles become more symmetrical and complete from shelf to basin (from western Ontario to central New York). Furthermore, each cycle contains distinctive biofacies and nektonic/pelagic faunas related to extinction and recolonization. The focus of this paper is on the small-scale cyclicity, its probable control by Milankovitch-forced sea-level oscillations, and how stacking patterns of meter-scale cycles can be used to define internal components of larger-scale sequences and estimate variations in relative sea level.